Effective Strategies for Digital-Based Archive and Document Management in Labuhanbatu High School - Suripto, Suripto; Zuhairi, Zuhairi; Manurung, Safaruddin; Astanti, Arinda; Harahap, Amin (International Journal Of Education, Social Studies, And Management (IJESSM), 2025)
This study explores the implementation of digital-based archive and document management strategies at Labuhanbatu High School, focusing on their effectiveness, usability, resource readiness, and operational challenges. Employing a mixed-methods approach, the research involved surveys, interviews, and observations with 30 participants comprising administrative staff, teachers, and IT personnel. The results revealed a high level of effectiveness (mean score: 4.2) and usability (mean score: 4.0), indicating that the system significantly improved document accuracy, retrieval speed, and user accessibility. However, the readiness of human resources (mean score: 3.8) and infrastructure limitations, such as insufficient storage and unstable internet, were identified as critical areas needing improvement. Organizational barriers, including the absence of formal SOPs and limited budget, also hindered optimal implementation. The findings suggest that comprehensive training, structured policy support, and phased infrastructure development are essential to sustain and scale digital archiving systems in educational institutions.